2008
DOI: 10.1002/jmv.21236
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B, C seroprevalence and delta viruses in HIV‐1 Senegalese patients at HAART initiation (retrospective study)

Abstract: The aim of this study was to determine hepatitis co-infection in a cohort of HIV infected patients at their inclusion in the Senegalese Initiative of ART Access. B, C, and D Hepatitis viruses serological markers were checked retrospectively on 363 stored plasma. For HBV, the Abbott laboratories equipment IMx was used to detect HBs Ag and anti Core Ab on negative HBs Ag samples. For HDV, anti Delta Ab was performed using the Abbott Murex Kit on all HBs Ag positive samples. For HCV, anti HCV Ab was detected by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
53
7
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 18 publications
21
53
7
2
Order By: Relevance
“…Our study results confirm the high prevalence of HBV infection among HIV patients in Côte d'Ivoire, and more generally in sub-Saharan Africa, as evidenced by most studies on the subject [10,13,[15][16][17][18][19][20][21][22] . Indeed, the prevalence of HBsAg and that of anti-HBcAb were respectively 13.4% and 72.9% in our patients.…”
Section: Discussionsupporting
confidence: 87%
“…Our study results confirm the high prevalence of HBV infection among HIV patients in Côte d'Ivoire, and more generally in sub-Saharan Africa, as evidenced by most studies on the subject [10,13,[15][16][17][18][19][20][21][22] . Indeed, the prevalence of HBsAg and that of anti-HBcAb were respectively 13.4% and 72.9% in our patients.…”
Section: Discussionsupporting
confidence: 87%
“…This figure is much lower than the figure obtained in our study (15.0%) (Figure 1). Our figure is also higher than what was obtained in similar studies in Kenya, East Africa (10.0%), Senegal, West Africa (1.6%) and South Africa (13.4%) [36][37][38] but lower than that of another Eastern Africa state, Tanzania (18.1%) 39 . The difference in prevalence could be due to differences in social behaviour of the individuals involved in this study and population size of the individual countries 40 …”
Section: Discussioncontrasting
confidence: 83%
“…This is obviously lower than the (16.8%) prevalence found by H. Ndiaye-Diop et al in Dakar in 2008(Diop-Ndiaye et al, 2008, but similar to the prevalence found by Lô et al, in 2012(Lô et al, 2012) (11%) among pregnant women living with HIV in Senegal. This decrease in seroprevalence could be explained by the effectiveness of vaccination against viral hepatitis B in Senegal and the systematic search for HBsAg in the assessment at prenatal consultations.…”
Section: Discussionsupporting
confidence: 69%
“…This is higher than the average found in available sources: 34 years in the study of Chloe L. Thio et al (Thio et al, 2013), 36 years in that of Attia et al (Attia et al, 2012), 32 years in that realized by Yitayih M. et al (Yitayih, Meseret, Fanaye, & Yeshambel, 2013), 38 years in the work of H. Diop-Ndiaye et al (Diop-Ndiaye et al, 2008). This could be explained by the youth of the overall African population but also by the fact that the population is sexually active at this age.…”
Section: Discussionmentioning
confidence: 74%